1987
DOI: 10.3406/bulmi.1987.7975
|View full text |Cite
|
Sign up to set email alerts
|

Origin of coffinite in sedimentary rocks by a sequential adsorption-reduction mechanism

Abstract: Coffinite is the dominant ore mineral in the tabular vanadium-uranium ores of the Tony M mine in the Henry Mountains Mineral Belt of the Colorado Plateau physiographic province of the United States. This ore body formed at a density-stratified solution interface between uranyl ion bearing-meteoric water and a saline fluid which was locally reducing. Uranium localization at this solution interface occurred by adsorption onto the surfaces of detrital minerals. This adsorption was related to the pH difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…In situ HRTEM images (Fig. 3) of a coffinite particle viewed along [1][2][3][4][5][6][7][8][9][10][11] zone axis clearly show the disruption of the lattice fringes with increasing dose. The lattice fringes are almost entirely lost at a dose of $0.38 dpa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ HRTEM images (Fig. 3) of a coffinite particle viewed along [1][2][3][4][5][6][7][8][9][10][11] zone axis clearly show the disruption of the lattice fringes with increasing dose. The lattice fringes are almost entirely lost at a dose of $0.38 dpa.…”
Section: Resultsmentioning
confidence: 99%
“…Coffinite occurs as a common alteration product of uraninite, UO 2+x , a natural analogue to the UO 2 in spent nuclear fuel [1][2][3]. Coffinite will form as an alteration product of spent nuclear fuel exposed to silica-rich ground water under reducing conditions [4][5][6][7][8][9]. The radiation response of coffinite is of even greater interest if it also incorporates transuranium elements, such as Pu, during the corrosion of UO 2 in spent nuclear fuel, particularly a mixed oxide fuel [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In many potential host rocks considered for a repository, silica concentrations are high enough to allow silicate precipitation (for instance, Si $ 10 À4 mol L À1 in the French candidate site -Meuse/Haute-Marne -for a future repository). Coffinite USiO 4 is therefore expected to be one of the potential alteration phases precipitating from SNF alteration under reducing Si-rich conditions [10][11][12][13][14][15]. Indeed, this mineral is widely observed in uranium ore deposits as an alteration phase of uraninite (natural analog of SNF [16]), particularly at Oklo (Gabon) [13,[17][18][19] and Cigar Lake (Canada) [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Mumpton and Roy [45] did not synthesize coffinite but uraninite and quartz and suggested coffinite may be metastable. Robit-Pointeau [41,46] suggested that (i) either the domain of thermodynamic stability of coffinite occurs in a narrow Eh/pH range, which would be different from the one predicted by the selected thermodynamic data [9], (ii) and/or coffinite precipitation is a kinetically controlled process and requires an unidentified precursor that could involve organic matter as reported from the uranium deposit [10,47,48]. Other coffinite synthesis protocols based on hydrothermal [49,50,7] or dry methods [51,52] are mentioned in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the phases coffinite (USiO 4 can form at hydrothermal conditions in geologic media [9]. For the case of coffinite formation, further mechanisms were found to apply [10]. These materials can be seen as potential candidates for uranium(IV) secondary phases formation during anoxic spent fuel alteration.…”
Section: Introductionmentioning
confidence: 99%